PENGARUH ORGANIZATION-BASED SELF-ESTEEM TERHADAP KOMITMEN ORGANISASIONAL DAN DAMPAKNYA PADA KINERJA PEGAWAI - Indrayanto, Adi (Jurnal Ekonomi Modernisasi, 2012)
The research aims to investigate and examine the mediating effect of organizational commitment on employees' performance, in the context of organization-based self-esteem at public organization. It is expected that the result of the research will provide an account to human resources management literature with regards to organizational commitment issue. The research is an explanatory study which attempts to examine and describe the variables using cross-sectional data analysis. Quantitative approach and in-depth interview are employed in this research. The research population consists of employees of public organization in Banyumas Area (Banyumas, Purbalingga, Cilacap, dan Banjarnegara regency). Total number of the respondents is 102 (response rate is 51%). Proportional random sampling is employed as the sampling technique of the research. Multiple regression analysis is performed for data analysis purpose. The result shows that organizational commitment has mediating effect on the relationship between organization-based self-esteem and employees' performance